A five years retrospective study of factors influencing outcome of major lower limb amputations - Marahanumaiah, Sudhir; Govindaiah, Sridhar (International Surgery Journal, 2020)
Background: The word amputation is derived from Latin -Amputare - to cut away. The amputation is indicated when the limb is considered as dead limb/ deadly limb/ dead loss limb. Often cases are referred to tertiary centre late, resulting in complications which requires surgical management. Aim of the study was to compare the outcomes of major lower limb amputations and to identify risk factors associated with mortality and morbidity following major lower limb amputations. Methods: A retrospective observational study was done for 5 years between January 2014 to November 2019, comprising 276 patients undergoing major lower extremity amputations. Adult patients undergoing lower extremity amputations for ischemic, infected or gangrenous lower limb were included and patients who underwent amputations for trauma or tumours were excluded. The data regarding comorbidities, postoperative complications, outcome of major lower limb amputations were evaluated. Results: 276 patients underwent lower limb amputations (above knee amputations (AKA)-127, below knee amputations (BKA)-134, forefoot amputations-15). Male patients outnumbered females (6.7:1) and most of them were of elderly age group (mean age 60.56 years). The most common indications for amputations in our study were peripheral vascular disease (120), diabetes (87), necrotizing fasciitis (37). The 1 year mortality rates following lower limb amputations in our study were 14% (BKA) and 34% (AKA). Conclusions: Lower limb amputations are associated with high mortality rates. Mortality can be expected in both the early and the late postoperative periods and is most probably related to serious comorbidities, such as renal and heart disease, rather than the level of amputation.